Canada's Contributions to the SWOT Mission – Terrestrial Hydrology(SWOT-C TH). Issue 2 (4th March 2019) - Pietroniro, Alain; Peters, Daniel L.; Yang, Daqing; Fiset, Jean-Michel; Saint-Jean, Robert; Fortin, Vincent; Leconte, Robert; Bergeron, Jean; Llanet Siles, Gabriela; Trudel, Mélanie; Garnaud, Camille; Matte, Pascal; et al.
Abstract: The origins of the Surface Water and Ocean Topography (SWOT) mission date back to the mid-1970s with the launch of GOES-3 and SEASAT. These missions were then followed in 1992 by the Topex-Poseidon satellite, then by Jason-1 (2001), OSTM/Jason-2 (2008), and Jason 3 (2016), a series of joint satellite missions between NASA and CNES with a goal to monitor global ocean circulation. The proposed new SWOT mission will provide 120-km-wide swath interferometric coverage with a 20-km-wide gap at the nadir. The SWOT measurements will consist of water surface elevations and water surface slopes covering nearly all of the earth's land surface at least once every 21 days. In 2010, NASA invited the Canadian Space Agency to contribute, and Canadian scientists welcomed the invitation to join the SWOT Science Definition Team and contribute to the experiments. The Canadian segment of the mission is known as the "SWOT-C" project. The SWOT satellite mission will provide unique opportunities in the Canadian context for water managers in both the public domain and in the private sector. This paper provides an overview of recent scientific progress by the SWOT-C Terrestrial Hydrology team, outlining current plans and progress towards applications and calibration post-launch.